Accuracy of information on the underlying cause of death: An analysis in Colombia during the COVID-19 pandemic in 2021. - Pablo Chaparro-Narváez; Jessika Alexandra Manrique Sanchez; Laura Berrio-Parra; Diana Carolina Urrego Ricaurte; Luis José Torres-Rojas; Nidia Patricia Orjuela Cantor; Claudia Patricia Mora Aguirre; Yesid Rojas Quevedo; Clara Suárez; Carlos Castañeda-Orjuela (PLoS ONE)
Objective This study aimed to estimate the accuracy of the underlying Cause of Death (CoD) in the original death certificate, compared with a gold standard certificate based on information from clinical records and relatives, in population deceased in Colombia during 2021. Methods A sample size of 806 deaths across 92 municipalities in Colombia were estimated from the pool of 326,833 original certificates provided by the National Department of Statistics. A two-stage stratified random sample with replacement was employed for selection. Information from medical records of the deceased and, when necessary, interviews with relatives or witnesses were used to determine CoDs on the gold standard certificate. We analyzed and compared the underlying CoD of the original and standard death certificates to estimate the level of accuracy. Measures of concordance, patterns of false positives and negatives, and a kappa value were utilized as metrics to evaluate the death certificates quality. Results Information was obtained from 776, representing 96% of the desired sample. The concordance between original and gold standard certificates, categorized according to the ICD-10 chapters, was found in 74%. Higher levels of agreement were observed for "codes for special COVID-19 situations" (kappa = 0.84) and neoplasms (kappa = 0.84). Higher levels of agreement were observed for "codes for special COVID-19 situations" (kappa = 0.84) and neoplasms (kappa = 0.84). Overestimation was identified for "circulatory system diseases" (Chapter IX); "pregnancy, childbirth and puerperium" (Chapter XV); "signs, symptoms, and poorly defined conditions" (Chapter XVIII) and "diseases of the respiratory system" (Chapter X), while underestimation in "diseases of the genitourinary system" (Chapter XIV) among CoD. The most significant variations in the fraction of mortality due to specific CoDs corresponded to "codes for special situations COVID-19". Conclusions The level of concordance between the original and gold standard death certificates was deemed adequate. However, improvements in the death certification process in Colombia are recommended, emphasizing the enhancement of training programs for health professionals.